Comparative perspectives of Africa style democracy - Thaela, Lefu (University of the Free State, 2020)
Africa is a continent that has for some time since independence progressed towards the new style of leadership. This leadership is inherited from the western style of leadership and as a result the continent democratised. Democracy in Africa has been researched in terms of the trends that took place since then. Issues that contribute to this democracy have been identified. They have been dealt with, but the continent seems not to be transforming, instead we see democracy back sliding in Africa. The study contributes towards the understanding of the African style of democracy, which maybe has to be accepted as one of its own kind that has some elements that have unique features from those of the original school of thought. The research investigates the perspectives of Africa style democracy in 5 African countries in comparison with the Swiss democracy. The research problem was premised on the characteristics of the democracy in this continent. Methodology of this study was a qualitative one using the secondary data that has been collected from various sources such as the catalogues, newspapers, books, journals and reports with the aim of investigating the characteristics of the democracy in Africa. The tenets of democracy being free, fair and regular elections, respect for human rights, freedom of media and checks on government, were used to find characteristics of the style of democracy. The study explored several theories including governance theory, cultural theory, participatory democracy, representative democracy, transformational leadership, great man theory, separation of powers theory, dictatorship theory and direct democracy. It is the conclusion in this study that Africa style democracy is characterised by disrespect for human rights, oppression of freedom of expression, elections manipulation and the supremacy of the executive. The findings of the research reject the “blanket” approach that democracy has to be the same throughout the global village; democracy has to be described and explained the way in which the citizens perceive it. The study concludes that democracy in Africa has got its own characteristics that are unique, comprising of authoritarian characteristics and the western democracy characters. The study therefore associates Africa type of democracy this type of democracy as a “mule type of democracy” and as a result it has to be accepted as it is.
Dissertation (M.A.(Governance and Political Transformation))--University of the Free State,  2020
Keywords: Democracy -- Africa; Africa style of democracy; Human rights -- Africa; Freedom of expression